Retrospective analysis of outcome of COVID positive patients undergoing emergency surgeries for acute general surgical conditions - Pratha, Anantha Ramani; Pustela, Mahesh Kumar; Kaniti, Vamsi Krishna; Shaik, Salma Begum; Pecheti, Tanmayi (International Surgery Journal, 2023)
Background: There is a significant impact of COVID-19 disease on medical and surgical community. Acute surgical emergencies had to be addressed inspite of several hardships to save the lives of patients. There is a need to understand the impact of COVID-19 disease on outcome of surgical emergencies. This study aimed to analyse the outcomes of COVID-19 patients with general surgical emergencies. Methods: This retrospective study was conducted on 50 patients undergoing emergency surgeries for acute general surgical pathologies in department of general surgery, Government General Hospital, Guntur from January 2021 to October 2021. Patients were divided into two groups, 25 patients who were COVID positive and 25 patients who were COVID negative. The outcomes assessed were mortality, multi organ dysfunction syndrome, surgery related complications and number of days of hospital stay. Results: Mortality was higher in COVID group when compared to non COVID group (32% vs. 8%). Average number of hospital stay was higher in COVID group than non Covid group (11.78 days vs. 8.43 days). COVID-19 patients developed MODS 2.88 times greater than non COVID patients (20% vs. 8%). Surgery related complications were higher in COVID-19 patients (28% vs. 8%). Conclusions: COVID positivity was associated with higher complications rate, higher mortality and increased duration of hospital stay.